Al2O3-Al2Cu double-strengthening-phase synergistically reinforced aluminum-based composite material and preparation method thereof
By using pretreated copper foil and aluminum plates in CuO-enhanced Al matrix composite materials for accumulation and stacking, and high-temperature aging treatment, Al2O3-Al2Cu double-strengthening phase is generated, which solves the problem of coarsing and segregation of the material during hot pressing and sintering, and achieves the improvement of the high strength and toughness of the material.
Patent Information
- Application Number
- CN202411876943.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing CuO-reinforced Al-based composite materials are prone to coarse Al2O3 and segregation of the second phase grain boundary during hot pressing sintering, and high strength and fracture toughness cannot be obtained simultaneously.
The nanoCuO layer was formed by pretreating the copper foil and wrapped in an aluminum plate for accumulation and stacking. Combined with high-temperature aging treatment, an Al2O3-Al2Cu double-strengthening phase synergistic reinforced aluminum-based composite material was generated.
The problems of Al2O3 coarsening and second phase grain boundary segregation were solved, which significantly improved the strength and toughness of Al-based composite materials, and maintained high temperature stability.
Smart Images

Figure CN119870150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material preparation, and particularly relates to an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material and a preparation method thereof. Background Art
[0002] With the further development of the aerospace industry, Al-based composite materials have become popular structural materials in this field due to their light weight, high plasticity, low expansion, high thermal conductivity and other properties. Introducing a reinforcing phase with excellent intrinsic physical properties such as high strength and high elastic modulus into the Al matrix or refining the grains to the nanoscale can significantly improve the tensile strength, elastic modulus and high temperature resistance of the composite material, broadening its application areas.
[0003] For example, after CuO is introduced into Al-based materials, Al2Cu and Al2O3 can be generated through in-situ reaction, achieving synergistic enhancement of the strengthening phase and the precipitation phase. At present, the main method of introducing CuO as a strengthening phase into aluminum-based materials is to generate a particle strengthening phase by substitution reaction by cumulative rolling or hot pressing sintering of aluminum and CuO powders.
[0004] Accumulative rolling generally adopts plate-plate or powder-plate rolling. In order to make CuO and aluminum plate undergo substitution reaction, CuO powder needs to be attached to the surface of copper plate or aluminum plate by cold spraying or hot spraying, which has the following defects:
[0005] (1) Adhesives are required to achieve effective adhesion of CuO powder;
[0006] (2) The copper plate is too thick to achieve the nano-enhancement effect, and the copper content is too high, so it is easy to break after multiple rolling;
[0007] (3) CuO powder easily causes uneven thickness of the reinforcement phase, affecting the uniformity of material properties.
[0008] Too high temperature or vacuum hot pressing during hot pressing sintering leads to coarsening of Al2O3 and energy mismatch at the Al2O3-A1 melt interface induces second phase grain boundary segregation. CuO-reinforced Al-based composites cannot simultaneously obtain high strength and fracture toughness, affecting the service use of the material.
[0009] Therefore, solving the problem of Al2O3 coarsening and second phase grain boundary segregation is the key to improving the comprehensive performance of CuO reinforced Al-based composites. Summary of the invention
[0010] In view of this, the object of the present invention is to provide an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material and a preparation method thereof, aiming to solve at least one technical problem in the background technology.
[0011] The present invention is achieved in that:
[0012] A method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material, the preparation method comprising the following steps:
[0013] The copper foil is preheated to form a copper oxide layer on the surface of the copper foil;
[0014] The aluminum plate is subjected to stress relief annealing and surface cleaning treatment, so that fresh aluminum atoms are exposed on the surface of the aluminum plate;
[0015] The copper foil is laid flat between two aluminum plates for the first rolling and welding to form an aluminum-based composite plate A;
[0016] The surface of the aluminum-based composite plate A is cleaned to expose highly active aluminum atoms, and then at least two groups of aluminum-based composite plates A are stacked and rolled and welded for a second time to form an aluminum-based composite plate B;
[0017] The aluminum-based composite plate B is subjected to cumulative lamination rolling, specifically, it is first cut in half and the surface is cleaned, and then it is laminated together, and then rolled and welded for the third time to form the aluminum-based composite plate C;
[0018] After the aluminum-based composite plate C is annealed, the aluminum-based composite plate C is subjected to cumulative rolling for at least 2 cycles to form an aluminum-based composite plate D, which is a nano-layered Al-CuO@Cu-Al plate;
[0019] The aluminum-based composite plate D is subjected to high-temperature aging treatment to generate an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material;
[0020] Among them, the specific operations of copper foil pretreatment are as follows:
[0021] Sandwich a copper foil with a thickness of 20 μm-30 μm between two pieces of sandpaper and grind it to remove the passivation layer on the surface of the copper foil;
[0022] The polished copper foil is placed in a muffle furnace, heated to 350°C-450°C in an air environment, and kept warm for 1h-4h to form a copper foil with a nano CuO layer on the surface.
[0023] Furthermore, the annealing treatment temperature after cumulative rolling is 120° C. to 160° C., and the time is 1 h to 2 h.
[0024] Furthermore, the stress annealing treatment is specifically performed as follows: cutting an aluminum plate with a thickness of 1.5 mm to 2 mm into a set size, annealing at 300° C. for 2 hours, and removing the stress in the aluminum plate by furnace cooling.
[0025] Furthermore, the surface cleaning treatment is specifically performed as follows: the surface of the aluminum plate or the corresponding aluminum-based composite plate is treated with a steel brush to remove the passivation layer on the surface of the aluminum plate to expose fresh metal with high activity, thereby forming a plate with frosted particles on the surface.
[0026] Furthermore, the rolling deformation during the first rolling and welding is 60%-65%; the rolling deformation during the second rolling and welding is 50%-55%; and the rolling deformation during the third rolling and welding is 45%-50%.
[0027] Furthermore, the total cumulative rolling process is 12 to 24 times.
[0028] Furthermore, an annealing treatment is performed after the cumulative rolling cycle is repeated for 5 to 6 times.
[0029] Furthermore, during the second rolling and welding, the number of stacked aluminum-based composite panels A is 2 to 5 groups.
[0030] Furthermore, the high temperature aging temperature is 450°C-550°C, and the time is 2h-12h.
[0031] Furthermore, when the copper foil is laid flat between two aluminum plates, space is left around the aluminum plates.
[0032] The second aspect of the present invention provides an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material obtained by the above preparation method.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention provides a method of using pretreated copper foil as an interlayer and combining cumulative rolling to obtain Al2O3-Al2Cu dual strengthening phase, thereby solving the problems of Al2O3 coarsening and second phase grain boundary segregation and synergistically improving the strength and toughness of Al-based composite materials.
[0035] 2. The present invention wraps a copper foil having a nano-CuO layer on the surface in an aluminum plate for cumulative rolling. The CuO layer, copper foil and aluminum plate are deformed synergistically to construct a uniformly distributed nano-layered Al-CuO@Cu-Al plate. Combined with high-temperature aging, a dispersed, uniformly layered and fine Al2O3-Al2Cu dual strengthening phase is formed.
[0036] 3. After high-temperature aging at 450°C-550°C, the present invention still has high strength and plasticity, proving that it has high-temperature resistance and high-temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the reinforcement phase in the aluminum-based composite material obtained in Example 1 of the present invention;
[0038] Figure 2 TEM image of the Al2O3-Al2Cu dual strengthening phase in the aluminum-based composite material obtained in Example 1 of the present invention;
[0039] Figure 3 This is a SEM image of the reinforcement phase in the aluminum-based composite material obtained when a 50 μm copper foil is used in Example 2 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0041] A method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material comprises steps S1 to S6.
[0042] S1, substrate pretreatment;
[0043] In a specific implementation, a copper foil with a thickness of 20 μm-30 μm is sandwiched between two pieces of sandpaper and gently polished to remove the passivation layer on the surface of the copper foil, so that the copper foil has a frosted texture; the polished copper foil is placed in a muffle furnace, heated to 350° C.-450° C. in an air environment, and kept warm for 1 h-4 h to form a copper foil with a nano CuO layer on the surface, namely CuO@Cu; the mesh number of the sandpaper is 1000 to 2000 mesh;
[0044] Aluminum plates with a thickness of 1.5mm-2mm are cut into set sizes, annealed at 300℃ for 2h, and furnace cooled to remove stress in the aluminum plates; the surface of the aluminum plates is then cleaned with a high-hardness 304 steel wire brush to remove the passivation layer on the surface of the aluminum plates and expose highly active fresh metal aluminum atoms, forming a plate with frosted particles on the surface.
[0045] S2. First rolling and welding
[0046] The copper foil and aluminum plate pretreated in step S1 are combined into a "hamburger"-like structure, specifically, the copper foil is laid flat between two aluminum plates, and a certain space is left around them (that is, the length and width of the aluminum plate are respectively larger than the length and width of the copper foil), and then the first rolling and welding are performed. When the rolling deformation is 55%-65%, Al-CuO@Cu-Al can achieve effective metallurgical bonding to form an aluminum-based composite plate A with 3 layers.
[0047] S3, second rolling and welding;
[0048] At least two groups of aluminum-based composite plates A are cut to the same size, and then the surface is cleaned to expose highly active aluminum atoms (which is the same as the surface cleaning step of the aluminum plate in step S1), and then the groups of aluminum-based composite plates A are stacked and rolled and welded for the second time. When the rolling deformation is 50%-55%, the second rolling is completed to form an aluminum-based composite plate B, which is an Al-CuO@Cu-Al plate containing 2-5 layers of CuO@Cu layers; in the specific implementation, the number m of stacked aluminum-based composite plates A is preferably 2 to 5 groups, and the number of layers is 3×m layers.
[0049] S4, the third rolling and welding;
[0050] First, the aluminum-based composite plate B is cut in half and the surface is cleaned (which is the same as the surface cleaning step of the aluminum plate in step S1), and then stacked together and rolled and welded for the third time. When the rolling deformation is 45%-50%, the third rolling is completed to form an aluminum-based composite plate C with 2×3×m layers.
[0051] S5, cyclic accumulation rolling;
[0052] The C annealing treatment of the aluminum-based composite plate softens the Al;
[0053] The half cutting, surface cleaning, lamination and rolling welding of step S4 are repeated to form an aluminum-based composite plate D, which is a nano-layered Al-CuO@Cu-Al plate;
[0054] In this step, the number of cumulative rolling cycles is increased, the number of layers N inside the plate increases exponentially, and the corresponding single layer thickness decreases rapidly to the nanometer scale in an exponential form. After the cyclic cumulative rolling, the total number of layers of the plate N = 3×m×2 n+1 , m is the number of aluminum-based composite plates A stacked in step S3, n is the number of cumulative rolling cycles in step S5, n=12 to 24;
[0055] In a specific implementation, an annealing treatment is performed after cumulative rolling is repeated 5 to 6 times. The reason is that after a certain number of rolling, the hardness of the plate increases, so annealing treatment is performed to soften the plate. The annealing temperature is 120°C to 160°C, and the time is 1h to 2h.
[0056] S6, high temperature aging treatment;
[0057] The aluminum-based composite plate D is subjected to high-temperature aging treatment at 450°C to 550°C for 2h-12h (preferably 2h-6h), so that the CuO@Cu film sandwiched in the nano-Al layer reacts with Al to form a dispersed Al2O3 reinforcement phase, and at the same time, Cu reacts with Al to form an Al2Cu reinforcement phase, and finally an Al2O3-Al2Cu dual reinforcement phase synergistically reinforced aluminum-based composite material is generated, which has the characteristics of both strength and toughness and high temperature resistance.
[0058] The present invention uses Al plates to wrap copper foil with a nano CuO layer on the surface and repeatedly rolls the copper oxide evenly. The copper oxide is evenly attached to the copper foil and can coordinate deformation with the Al plate during the rolling process, so that CuO is evenly distributed in the matrix, and a nano-layered Al-CuO@Cu-Al plate with even internal distribution is constructed; and then through aging, the copper foil with a thin CuO layer on the surface sandwiched between the Al plates reacts in situ with the Al matrix to generate dispersed and evenly distributed fine Al2O3 strengthening phases and Al2Cu strengthening phases. This reaction process is a solid phase reaction with low temperature, which can effectively solve the problem of coarsening of the Al2O3 strengthening phase, and finally achieve the effect of improving the comprehensive performance of the material. The specific examples of the present invention prove that it is completely feasible from material design to preparation process, and the cost is low, and the material performance is significantly improved.
[0059] Example 1
[0060] A method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material comprises the following steps:
[0061] S1. Cut a copper foil with a thickness of 20 μm into a size of 25 mm*35 mm, cut a 1000-mesh sandpaper into a size of 30 mm*40 mm, and use two pieces of sandpaper to sandwich the copper foil and gently polish it to remove the passivation layer on the surface of the copper foil until the surface of the copper foil presents a frosted texture; place the polished copper foil in a muffle furnace for heat treatment, heat it to 400°C in an air environment, and keep it warm for 3 hours to form a copper foil with a nano CuO layer on the surface; cut an aluminum plate with a thickness of 1.7 mm into 30 mm*40 mm, anneal it at 300°C for 2 hours, and remove the stress in the aluminum plate with furnace cooling; then clean the surface of the aluminum plate with a high-hardness 304 steel wire brush, remove the passivation layer on the surface of the aluminum plate, expose fresh metal aluminum atoms with high activity, and form an aluminum plate with frosted particles on the surface;
[0062] S2, laying the copper foil treated by S1 between two aluminum plates treated by S1, performing the first rolling and welding, and stopping when the rolling deformation reaches 60%, to form an aluminum-based composite plate A, which is an Al-CuO@Cu-Al alloy;
[0063] S3, cutting three groups of aluminum-based composite plates A into the same size, cleaning the surface of the aluminum-based composite plates A with a steel brush to expose the highly active aluminum atoms, and then stacking the groups of aluminum-based composite plates A neatly and performing a second rolling and welding, and stopping when the rolling deformation reaches 55%, to form an Al-CuO@Cu-Al plate containing three CuO@Cu layers, recorded as aluminum-based composite plate B;
[0064] S4, first cut the aluminum-based composite plate B in half, clean the surface of the aluminum-based composite plate B with a steel brush to expose the highly active aluminum atoms, then overlap the two together, perform the third rolling and welding, and stop when the rolling deformation reaches 45%, to form an aluminum-based composite plate C;
[0065] S5, the aluminum-based composite plate C is annealed at 150° C. for 1 h to soften Al; the half-cutting, surface cleaning, lamination and rolling welding of step S4 are repeated 24 times to form an aluminum-based composite plate D; and the annealing treatment is repeated after every 5 to 6 cumulative lamination passes;
[0066] S6. The aluminum-based composite plate D was subjected to high-temperature aging treatment at 540°C for 6h, so that the CuO@Cu film sandwiched in the nano-Al layer reacted with Al to form a dispersed Al2O3 strengthening phase. At the same time, Cu reacted with Al to form an Al2Cu strengthening phase, forming an Al2O3-Al2Cu dual strengthening phase, and finally generating an Al2O3-Al2Cu dual strengthening phase synergistically reinforced aluminum-based composite material.
[0067] The aluminum-based composite material prepared in this embodiment was subjected to a room temperature quasi-static tensile test in accordance with the GB / T228.1-2010 standard to measure its tensile strength and elongation after fracture to determine the strength and plasticity of the aluminum-based composite material.
[0068] The strengthening phase in the aluminum-based composite material obtained in this embodiment was observed microscopically, and its SEM image is as follows: Figure 1 As shown, its TEM image is as follows Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the strengthening phase is distributed along the layers and appears as thin lines.
[0069] Example 2
[0070] The present embodiment is a method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material. Based on Example 1, the thickness of the copper foil in step S1 is adjusted to 10μm, 30μm, 40μm, and 50μm, respectively, and recorded as Example 2-1, Example 2-2, Example 2-3, and Example 2-4, and other reaction conditions remain unchanged.
[0071] The experiments of each variable of Example 1 and this example were repeated 3 times, and the mechanical properties and microscopic results of the strengthening phase were measured and compared. The comparison results are shown in Table 1.
[0072] Table 1
[0073]
[0074] Example 1, Example 2-1 to Example 2-4 compare the effects of different copper foil thicknesses on the morphology of the reinforcement phase and the performance of the final product. It can be seen from the data in Table 1 that with increasing thickness, the strength increases and the plasticity gradually decreases. The reason is that the coarsening of the reinforcement phase leads to a decrease in the work hardening ability and a decrease in the elongation of the sheet. When the copper foil thickness is 20μm to 30μm, the aluminum-based composite material finally obtained maintains a strength of more than 350Mpa and a plasticity of more than 30%, so the copper foil thickness is preferably 20μm to 30μm.
[0075] The strengthening phase in the aluminum-based composite material made of 50 μm copper foil in this embodiment was observed microscopically, and its SEM image is as follows: Figure 3 As shown. Figure 3 It can be seen that the reinforcement phase is in the form of coarse-grained dispersion.
[0076] Example 3
[0077] The present embodiment is a method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material. The copper foil pretreatment process in step S1 is adjusted on the basis of Example 1, and they are respectively recorded as Examples 3-1 to 3-11. Other reaction conditions remain unchanged. The performance of the aluminum-based composite material finally obtained under different pretreatment conditions is compared.
[0078] The experiments of each variable of Example 1 and this example were repeated 3 times, and the mechanical properties and microscopic results of the strengthening phase were measured and compared. The comparison results are shown in Table 2.
[0079] Table 2
[0080]
[0081]
[0082] Example 1, Example 3-1 to Example 3-4, compare the effects of pretreatment of copper foil under different temperature conditions on the morphology of the strengthening phase and the performance of the final product. It can be seen from the data in Table 2 that as the temperature increases, the material strength gradually increases. The reason is that the oxide layer of the copper foil thickens and more Al2O3 strengthening phases are generated; however, when the temperature increases to above 500°C, the copper foil turns gray; therefore, the heat treatment temperature of the copper foil is preferably 350°C to 450°C. In this range, the aluminum-based composite material finally obtained maintains a strength of more than 310Mpa and a plasticity of more than 30%;
[0083] In Example 1, Example 3-5 to Example 3-8, the effects on the morphology of the reinforcement phase and the performance of the final product under different heat treatment time conditions are compared. It can be seen from the data in Table 2 that as time increases, the strength of the aluminum-based composite material gradually increases and the plasticity gradually decreases. The reason is that the oxide layer generated by the copper foil is too thick, and the reinforcement phase generated after the reaction with the Al plate is coarse. According to research, the heat treatment time of the copper foil is preferably 1h to 4h, and more preferably 2h to 3h. Within this range, the aluminum-based composite material finally obtained maintains a strength of more than 310Mpa and a plasticity of more than 30%;
[0084] In Example 1, Example 3-9 and Example 3-11, the effects of grinding and heat treatment on the morphology of the strengthening phase and the performance of the final product are compared. It can be seen from the data in Table 2 that after removing the grinding and / or heat treatment, the strength and toughness of the aluminum-based composite material finally obtained are greatly reduced compared with Example 1. The reasons are as follows: (1) During the storage process, a passivation film will form on the surface of the copper foil. If it is directly oxidized without being polished, the required heat treatment temperature will increase significantly. The oxidation effect is not good in the range of 350°C to 450°C. When the oxidation temperature is further increased, the copper foil will be oxidized to ash, and the effect of forming copper oxide on the surface cannot be achieved; (2) The purpose of heat treatment is to react copper with oxygen in the air to form copper oxide. If high-temperature oxidation is not performed, the subsequent strengthening phase will only contain Al2Cu without Al2O3.
[0085] Example 4
[0086] The present embodiment is a method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material. The rolling deformation in the rolling and welding in steps S2 to S5 is adjusted on the basis of Example 1, and are respectively recorded as Example 4-1 to Example 4-8. The other reaction conditions remain unchanged, and the performance of the aluminum-based composite material finally obtained under different rolling deformation conditions is compared.
[0087] The experiments of each variable of Example 1 and this example were repeated 3 times, and the mechanical properties and microscopic results of the strengthening phase were measured and compared. The comparison results are shown in Table 3.
[0088] Table 3
[0089]
[0090] Example 1, Example 4-1 to Example 4-3, compare the effects of different first rolling deformation conditions on the morphology of the strengthening phase and the performance of the final product. It can be seen from the data in Table 3 that when the first rolling deformation is too small (50%), delamination occurs after the lap rolling; as the first rolling deformation further increases, the strength and plasticity of the material are synergistically improved, because the interface bonding is good and the strengthening effect is improved; therefore, the first rolling deformation is preferably 55% to 65%, preferably 60% to 65%;
[0091] Example 1, Example 4-4 to Example 4-5, compare the effects of different second rolling deformation conditions on the morphology of the strengthening phase and the performance of the final product. It can be seen from the data in Table 3 that when the second rolling deformation is too small (50%), the interface bonding after the lap rolling is poor and the overall stratification occurs; as the second rolling deformation increases further, the sample cracks during the rolling process. The reason is that the reduction is too large, the deformation releases heat energy, and the strengthening phase is generated during the deformation process, causing the strengthening phase segregation and cracking; therefore, the second rolling deformation is preferably 50% to 55%;
[0092] Example 1, Example 4-6 to Example 4-8 compare the effects of different third rolling deformation conditions on the morphology of the strengthening phase and the performance of the final product. It can be seen from the data in Table 3 that when the third rolling deformation is too small (40%), the interface bonding is poor and the overall stratification occurs; as the third rolling deformation increases further, the interface bonding effect is good, but the sample will also crack if it is too large. The reason is that the reduction is too large, the deformation releases heat energy, and the strengthening phase is generated during the deformation process, causing segregation and cracking of the strengthening phase; therefore, the third rolling deformation is preferably 45% to 50%.
[0093] Example 5
[0094] The present embodiment is a method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material. The number of cumulative rolling cycles in step S5 is adjusted on the basis of Example 1, and are respectively recorded as Example 5-1 to Example 5-5. Other reaction conditions remain unchanged. The performance of the aluminum-based composite material finally obtained under different cycle times is compared.
[0095] The experiments of each variable of Example 1 and this Example were repeated 3 times, and the mechanical properties and microscopic results of the strengthening phase were measured and compared. The comparison results are shown in Table 4.
[0096] Table 4
[0097]
[0098] Example 1, Example 5-1 to Example 5-5 compare the effects of different cycle passes on the morphology of the strengthening phase and the performance of the final product. It can be seen from the data in Table 4 that as the number of cycles increases, the material strength gradually increases. The reason is that as the number of cycles increases, the material grains gradually become finer and the strengthening effect gradually improves; but when the number of cycles increases to 26 times, the layered structure is destroyed and the plasticity decreases sharply, so the preferred number of cycles is 12 to 24 times.
[0099] Example 6
[0100] The present embodiment is a method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material. The high-temperature aging treatment temperature and time in step S6 are adjusted on the basis of Example 1, respectively recorded as Example 6-1 to Example 6-8, and other reaction conditions remain unchanged. The performance of the aluminum-based composite material finally obtained under different high-temperature aging treatment conditions is compared.
[0101] The experiments of each variable of Example 1 and this Example were repeated 3 times, and the mechanical properties and microscopic results of the strengthening phase were measured and compared. The comparison results are shown in Table 5.
[0102] Table 5
[0103]
[0104]
[0105] Example 1, Example 6-1 to Example 6-8, compare the effects on the morphology of the strengthening phase and the performance of the final product under different high-temperature aging treatment conditions. From the data in Table 5, it can be seen that as the aging treatment time increases, the strength and plasticity of the aluminum-based composite material obtained increase. When the time exceeds 6h, the strength and plasticity no longer increase and slightly decrease, so the high-temperature aging time is 2h to 12h, preferably 2h to 6h; as the high-temperature aging temperature increases, the strength and plasticity of the aluminum-based composite material obtained first increase and then decrease synchronously, especially when the temperature rises to above 550℃, the strengthening phase coarsens and the strengthening effect decreases, so the high-temperature aging temperature is set to 500℃ to 550℃.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material, characterized in that: The preparation method comprises the following steps: The copper foil is preheated to form a copper oxide layer on the surface of the copper foil; The aluminum plate is subjected to stress relief annealing and surface cleaning treatment, so that fresh aluminum atoms are exposed on the surface of the aluminum plate; The copper foil is laid flat between two aluminum plates for the first rolling and welding to form an aluminum-based composite plate A; The surface of the aluminum-based composite plate A is cleaned to expose highly active aluminum atoms, and then at least two groups of aluminum-based composite plates A are stacked and rolled and welded for a second time to form an aluminum-based composite plate B; The aluminum-based composite plate B is subjected to cumulative lamination rolling, specifically, it is first cut in half and the surface is cleaned, and then it is laminated together, and then rolled and welded for the third time to form the aluminum-based composite plate C; After the aluminum-based composite plate C is annealed, it is subjected to cumulative rolling for at least 2 cycles to form an aluminum-based composite plate D, which is a nano-layered Al-CuO@Cu-Al plate; The aluminum-based composite plate D is subjected to high-temperature aging treatment to generate an aluminum-based composite material synergistically reinforced by Al2O3-Al2Cu dual strengthening phases; Among them, the specific operations of copper foil pretreatment are as follows: Sandwich a copper foil with a thickness of 20 μm-30 μm between two pieces of sandpaper and grind it to remove the passivation layer on the surface of the copper foil; The polished copper foil is placed in a muffle furnace, heated to 350°C-450°C in an air environment, and kept warm for 1h-4h to form a copper foil with a nano CuO layer on the surface.
2. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: The annealing treatment temperature after cumulative rolling is 120° C. to 160° C., and the time is 1 h to 2 h.
3. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: The specific operation of the stress annealing treatment of the aluminum plate is: cutting the aluminum plate with a thickness of 1.5mm-2mm into a set size, annealing at 300°C for 2h, and removing the stress in the aluminum plate with furnace cooling; the specific operation of the surface cleaning treatment is: steel brushing the surface of the aluminum plate or the corresponding aluminum-based composite plate to remove the passivation layer on the surface of the aluminum plate to expose highly active fresh metal, forming a plate with frosted particles on the surface.
4. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: The rolling deformation during the first rolling and welding is 60%-65%; the rolling deformation during the second rolling and welding is 50%-55%; and the rolling deformation during the third rolling and welding is 45%-50%.
5. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: The total number of cumulative rolling is 12 to 24 passes.
6. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1 or 5, characterized in that: After the cumulative rolling cycle is repeated for 5 to 6 times, an annealing treatment is performed. The annealing condition is 120° C. to 160° C. and the time is 1 hour to 2 hours.
7. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: During the second rolling and welding, the number of stacked aluminum-based composite panels A is 2 to 5 groups.
8. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: The high temperature aging temperature is 450°C-550°C, and the time is 2h-12h.
9. The method for preparing an Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material according to claim 1, characterized in that: When the copper foil is laid flat between two aluminum plates, space is left around the aluminum plates.
10. An Al2O3-Al2Cu dual-strengthening phase synergistically reinforced aluminum-based composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high-toughness aluminum base nanometer composite material
CN105779915A
Plate strip for automobile water tank and manufacturing method
CN113145644A
High-strength and high-plasticity Cu / Al2O3 layered composite board
CN116765129A
Preparation method of copper alloy with double heterostructures
CN118186321A
Aluminum copper clad material
US20130071686A1